THE CONTENT OF PROFESSIONAL TRAINING OF SPECIALISTS OF LEGAL PROFILE: HISTORICAL AND PEDAGOGICAL ASPECT - Yasinskui, Vyacheslav (Continuing Professional Education: Theory and Practice, 2019)
The author analyzes different approaches to the definition of the content of the professional training of law faculty specialists in higher educational institutions of Ukraine at the beginning of the 20th century, including: the adoption of normative acts and basic provisions of university statutes, the creation of new professionally oriented departments, the spread of specialization and the variability of academic disciplines. The article shows the expediency of opening the legal department with women’s courses in the economic and commercial direction, as well as the necessity of opening the first higher non-governmental educational institutions. The specifics of the construction of the educational process in the training of legal professionals are described. Also author described the specific features of the content of the legal education of the time, in particular: the study of the main provisions of foreign law, the introduction of the leading ideas of philosophical and economic doctrine, the history of law.null In the article the author focuses on the activities of the legal faculties of the classical universities of the early twentieth century; noted that the leading form of teaching at that time was a lecture, the only source of obtaining legal knowledge - an outline, the dominant method of teaching - dogmatic. A parallel is made in the analysis of the content of the professional training of legal professionals in the time interval as one century. The shortcomings of the content of the professional training of legal specialists were noted, the necessity of its modernization in the modern conditions of the reform of the system of higher education in general was proved. The article analyzes the modern educational process of higher legal education in Ukraine and states that it is overloaded with normative and theoretical studies.